Toward Net Zero Carbon Buildings Development in Vietnam: Fostering Sustainable Mindsets Among The Future Construction Workforce - To, Thi Huong Quynh; Ta, Dang Bach (International Journal of Sustainable Construction Engineering and Technology, 2025)
Developing a sustainability mindset among future construction professionals is critical for advancing Net Zero Carbon Buildings (NZCB) in Vietnam. This study analyses 613 student survey responses using one-way and two-way ANOVA to examine differences in Sustainability awareness and Benefits, Motivation & Opportunities, and Barriers related to Sustainable mindset across academic years and majors. The results reveal significant gaps: early-year students demonstrate notably lower awareness than final-year students and former students. Similarly, students in Construction Management show less awareness compared to those in Architecture and Civil Engineering. However, significant differences in perceived Benefits, Motivation & Opportunities, and Barriers were found only between early-year and more advanced students, rather than across majors. These findings highlight the importance of integrating sustainability education early in university curricula and tailoring it to specific professional tracks. The results provide a valuable evidence base for shaping policies and educational reforms to cultivate sustainability competencies among Vietnam’s future construction workforce, thereby supporting the national NZCB agenda.